Method for producing a recombinant thermostable geobacillus T1 lipase - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Leow, Thean Chor (2008)
The present invention provides a method for producing a recombinant thermostable Geobacillus T1 lipase comprising (a) expression of the thermostable Geobacillus T1 lipase without the signal peptide (amino acids) as a GST-fusion protein in a prokaryotic host strain, and (b) affinity chromatography purification of said GST-fusion protein.